Leveraging Global Experiences in Sustainable Mining Development: Strategies and Practical Applications for Afghanistan - Yar, Fayaz Gul Mazloum; Sail, Ezat Ullah (Syntax Corporation, 2025)
This study investigates global experiences in sustainable mining development and explores their applicability to Afghanistan, a resource-rich but fragile state. With its vast mineral reserves, Afghanistan holds significant potential for economic growth. However, unregulated mining practices have led to environmental degradation, socioeconomic inequities, and governance challenges. The research adopts a mixed-method approach, combining thematic reviews, case studies, and quantitative analysis to synthesize best practices from leading mining nations like Australia, Canada, Chile, and Botswana. Findings reveal critical gaps in Afghanistan’s environmental management, community engagement, and revenue allocation. Practical recommendations include adopting environmental monitoring systems, establishing transparent governance structures, and fostering community participation to align with global standards. The study bridges the gap between global frameworks and Afghanistan’s socio-political realities, offering a roadmap for sustainable resource management. This novel contribution emphasizes adaptive strategies tailored to fragile contexts, addressing both academic and practical dimensions of sustainable development.